Artes e design para o enem em ações formativas integradas - Reis, Thamires Maitra Rodrigues Dos (2019)
Enem is the largest exam carried out in the country with 6,774,8991 enrollments in 2018 and is today the main form of access to higher education. Among the curricular skills covered in the exam is the discipline of arts in the area of ​​code languages ​​and their technologies. The Integrated Training Actions (AFIN) project of the Dean of Extension of the Federal University of Uberlândia annually offers classes free of charge with preparatory content for the national high school exam (ENEM), assisting candidates who are taking or coming from the public school system . In this project, we seek to observe the practice of undergraduate degrees within the project, specifically in the discipline of arts, focusing on art education, using design methodologies for this. This work presents, from the research, the support material created for the arts discipline of the AFIN project, presenting design and its methodologies as a possibility of a pedagogical approach since design is interdisciplinary and is directly related to art, developing both manual as well as mental skills, allowing the junction of critical and creative thinking. This research work is of a theoretical-practical nature. It is based on bibliographic surveys, critical readings, and analyzes seeking to think of pedagogical approaches and methodologies of arts and design to support art classes within the AFIN program.